Kemampuan Akses Pengusaha Kecil, Menengah dan Koperasi Terhadap Lembaga Keuangan Mikro Di Tarakan - Kaujan, Kaujan (Ekonomika, 2010)
The purpose of this study to determine the accessibility capabilities of Micro Small and Medium Enterprises (MSMEs)and the cooperative of Microfinance Institutions (MFIs), based on the development aspects of the credit amount received or disbursed to SMEs and Cooperatives and SMEs and Cooperatives the ability to repay (Capacity Building). Then find accessibility SMEs to MFIs, if measured in terms of sustainability (sustainable) of MFIs in providing financial services. Based on the amount of the loan, the ability of accessibility for SMEs and Cooperatives Fund Program of Integrated economy in Tarakan City declining trend pattern every year. Based on the loan amount, it turns out the perpetrators ability accesibility for SMEs and Cooperatives MFI-patterned PEMP City also declined, and predicted it would end the program (unsustainable) in the year 2011 due to run out of capital due to bad credit problems (aspects of the character and capacity building). Different Results shown by BMT Al-Fath that base on the amount of the loan, turns out the perpetrators ability accesibility for SMEs and Cooperatives BMT Al-Fath Tarakan increased.Â Key Words: Access to Credit, Small and Medium Enterprises, Micro Finance